Ultrasensitive conformal electronic skin based on microporous structure and preparation method thereof

By introducing copper calcium titanate nanoparticles and microporous structures into the sensing layer of the electronic skin, and using screen printing technology, the problems of low sensitivity and difficulty in conformity of capacitive electronic skin are solved, achieving high sensitivity, dynamic load detection and curved interface conformity.

CN119708609APending Publication Date: 2025-03-28YANGTZE DELTA REGION INST (QUZHOU) UNIV OF ELECTRONIC SCI & TECH OF CHINA
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411812942.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing capacitive electronic skin has low sensitivity and is difficult to conform to the curved application interface.

Method used

Ultra-sensitive, conformable electronic skin is prepared by introducing huge dielectric constant copper calcium titanate nanoparticles and microporous structures into the sensing layer, and using screen printing technology to obtain an ultra-thin porous composite film.

Benefits of technology

It realizes high sensitivity detection without affecting ambient temperature and humidity, and has the ability to detect dynamic loads. At the same time, due to its ultra-thin characteristics, it can be conformed with various curved interfaces.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708609A_ABST
    Figure CN119708609A_ABST
Patent Text Reader

Abstract

The invention relates to ultra-sensitive and conformal electronic skin based on a microporous structure and a preparation method, and aims to improve the sensitivity and the wearable performance of the electronic skin for sensing and monitoring. According to the main scheme, sodium chloride soluble crystal particles with microscale and copper calcium titanate nanoparticles with giant dielectric constant are prepared. The soluble sodium chloride crystal particles are combined with a polydimethylsiloxane matrix formed by mixing calcium copper titanate nanoparticles, an organic / inorganic composite film is obtained in a silk-screen printing mode, then the film is immersed in water, the soluble sodium chloride crystal particles are etched away, and the compressible microporous film is obtained. The upper and lower surfaces of the film are sprayed with electrodes and are connected with leads to prepare the ultra-sensitive electronic skin. The electronic skin has high sensitivity and high linearity, is not influenced by environment temperature and humidity, can detect dynamic load, and is suitable for the flexible wearable field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of flexible electronic technology, and in particular to an ultra-sensitive and conformable electronic skin based on a microporous structure. Background Art

[0002] Electronic skin is a type of sensing system that mimics the specific functions of human skin. It has the characteristics of sensing external pressure, tension, temperature and humidity, and is widely used in human-computer interaction, health care, motion detection and other fields. However, the sensing materials that make up the electronic skin are easily affected by other variables. For example, although the electronic skin built based on piezoresistive characteristics has the characteristics of high sensitivity during the detection process, the resistive material is easily affected by the ambient temperature. The increase or decrease in temperature will cause the detection signal to be inaccurate. The electronic skin built based on friction points or piezoelectric characteristics has a simple structure and can perform passive detection, but its test results are not only affected by humidity, but also have the disadvantage of being unable to detect dynamic loads. As for the electronic skin based on the capacitance change characteristics, according to the capacitance formula: C=ε0ε r From S / 4πkd, it can be seen that the capacitance test is only related to the thickness of the material when the dielectric constant of the sensing material remains unchanged, which allows the detection process to avoid being interfered by temperature and humidity. At the same time, capacitive electronic skin can freely detect dynamic loads. However, due to the limitations of the dielectric constant and structure of the material, the sensitivity of capacitive electronic skin is often low. By introducing nanoparticles with high dielectric constants inside the sensing layer, its dielectric constant can be effectively improved, but its compressibility has not been improved and often even decreased; the introduction of fine microporous structures can improve the sensitivity of such sensors, but at the same time increases the thickness of the sensing layer, reducing its flexibility as an electronic skin, and making it difficult to conform to the curved application interface. Summary of the invention

[0003] In order to overcome the shortcomings of existing capacitive electronic skins, such as low sensitivity and difficulty in conforming, the present technical solution provides an ultra-sensitive electronic skin based on a microporous structure and a preparation method. By introducing copper calcium titanate nanoparticles and a microporous structure with a giant dielectric constant into the sensing layer, the dielectric constant and compressibility of the sensing layer are improved at the same time, and an ultra-thin porous composite film is obtained by screen printing. The electronic skin prepared from the film is not only unaffected by ambient temperature and humidity, but also has relatively sensitive sensing characteristics for dynamic loads. At the same time, due to its ultra-thin characteristics, it can conform to various curved interfaces.

[0004] In order to achieve the above purpose, the present invention adopts the following technical solutions:

[0005] The present invention provides a method for preparing an ultra-sensitive and conformable electronic skin based on a microporous structure, comprising the following steps:

[0006] Step 1, adding titanium tetrachloride solution dropwise into ammonia water in a fume hood, adjusting the pH value of the solution to 8.0 to obtain white titanium dioxide gel, then dissolving the titanium dioxide gel in a mixed solution of oxalic acid, calcium carbonate, copper nitrate and acetone, filtering to obtain a blue colloid, and then calcining the blue colloid in a muffle furnace to obtain copper calcium titanate crystal powder;

[0007] Step 2, pouring sodium chloride and copper calcium titanate particles into a mortar for ball milling, pouring the mixed powder after ball milling into polydimethylsiloxane for uniform dispersion, and then coating the mixed viscous solution by screen printing to obtain a composite film material;

[0008] Step 3: Cut the composite film material of appropriate size and place it in warm water to dissolve the sodium chloride microscopic particles in the film to form a microporous structure, thereby obtaining an organic / inorganic composite microporous film. Electrodes are sprayed on the upper and lower surfaces of the film and connected to wires to make ultra-sensitive electronic skin.

[0009] In the above scheme, in step 1, the calcination temperature in step 1 is 750° C., and the calcination atmosphere is air.

[0010] In the above scheme, the amounts of oxalic acid, calcium carbonate, copper nitrate, acetone and deionized water in step 1 are 0.08 mol, 0.01 mol, 0.03 mol, 40 ml and 100 ml respectively.

[0011] In the above scheme, in step 2, the calcium copper titanate needs to be ultrasonically treated and dried in a grinder.

[0012] In the above scheme, the screen printing mesh size in step 2 is 50 meshes.

[0013] In the above scheme, the size of the film cut in step 3 is 1*1*0.2mm 3 .

[0014] In the above scheme, the electrode material sprayed in step 3 is a mixture of silver nanoparticles and acrylic acid.

[0015] The present invention also provides an ultra-sensitive electronic skin based on a microporous structure obtained by the ultra-sensitive electronic skin based on a microporous structure and the preparation method thereof.

[0016] In combination with the above technical solutions and the technical problems solved, the advantages and positive effects of the technical solutions to be protected by the present invention are as follows:

[0017] 1. The preparation method of the present invention is ingeniously designed, finely structured, and simple in process. It uses soluble sodium chloride microparticles to give the film a high porosity, thereby obtaining good compressibility and improving the sensitivity of the electronic skin. It uses the high dielectric constant of copper calcium titanate to further improve the sensitivity of the electronic skin, solving the technical problem of low sensitivity of traditional capacitive electronic skin, and realizing the perception of micro-scale deformation of capacitive electronic skin in flexible electronic devices. It uses screen printing to solve the problem of thick sensing layer thickness, and realizes the conformal application of ultra-thin sensing layer in electronic skin. The raw materials required for the preparation of the electronic skin are abundant, low in cost, fast in preparation, and easy to industrialize.

[0018] 2. The technical solution of the present invention fills the technical gap in the industry at home and abroad: At present, electronic skin used for intelligent perception is mainly based on electrical signals such as resistance, capacitance, triboelectricity, and piezoelectricity for signal detection. Although the electronic skin built based on piezoresistive characteristics has the characteristics of high sensitivity during the detection process, the resistance material is easily affected by the ambient temperature, and the increase or decrease in temperature will cause inaccurate detection signals; while the electronic skin built based on friction points or piezoelectric characteristics has a simple structure and can perform passive detection, but its test results are not only affected by humidity, but also have the disadvantage of being unable to detect dynamic loads. Electronic skin based on the capacitance change characteristics, according to the capacitance formula: C=ε0ε r From S / 4πkd, it can be seen that the capacitance value test is only related to the thickness of the material when the dielectric constant of the sensing material remains unchanged, which allows the detection process to avoid interference from temperature and humidity. However, due to the limitations of the dielectric constant and structure of the material, the sensitivity of capacitive electronic skin is often low. Through the design of mesoscopic micropores and the introduction of high dielectric parameter materials, we have made the electronic skin not only have high sensitivity, but also be unaffected by ambient temperature and humidity, and have the ability to detect dynamic loads. At the same time, the ultra-thin composite film obtained by screen printing technology has unique flexibility and bendability, which makes it truly applicable to electronic skin and conformal monitoring with the application interface, promoting the development of thin film sensing technology.

[0019] Third, the technical solution of the present invention overcomes technical prejudice: For a long time, it has been difficult for electronic skin used for intelligent perception to meet technical requirements such as high sensitivity, high linearity, no influence of temperature and humidity, and dynamic detection. For example, although resistive pressure electronic skin has high sensitivity, it is limited by its conductive material, and the conductive material is easily interfered by the temperature signal during the sensing process; for electronic skin based on triboelectricity and piezoelectricity, the humidity environment has a decisive influence on its signal value; and due to the limitation of the sensing structure, the sensitivity and linearity of capacitive electronic skin have always been low. This solution, through the design of mesoscopic micropores and the introduction of high dielectric parameter materials, makes the electronic skin not only have high sensitivity, but also not be affected by ambient temperature and humidity, and have the ability to detect dynamic loads, which promotes the development of flexible electronic skin sensing technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments of the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0021] Figure 1 This is a flow chart of an ultra-sensitive electronic skin based on a microporous structure and a preparation method provided by an embodiment of the present invention;

[0022] Figure 2 is the XRD pattern of the copper calcium titanate nanoparticles obtained in Example 1 of the present invention;

[0023] Figure 3 is a surface optical microscope image of the porous film obtained in Example 1 of the present invention;

[0024] Figure 4 is a light microscopic image of the thickness of the porous film obtained in Example 1 of the present invention;

[0025] Figure 5 is a mechanical-electrical response diagram of the electronic skin obtained in Example 1 of the present invention;

[0026] Figure 6 is a sensitivity diagram of the electronic skin obtained in Example 1 of the present invention;

[0027] Figure 7 is a response time diagram of the electronic skin obtained in Example 1 of the present invention;

[0028] Figure 8 This is a stability diagram of the electronic skin obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0029] The following is a detailed description of the embodiments of the present invention. Although the present invention will be described and illustrated in conjunction with some specific embodiments, it should be noted that the present invention is not limited to these embodiments. On the contrary, modifications or equivalent substitutions made to the present invention should all be included in the scope of the claims of the present invention.

[0030] In addition, in order to better illustrate the present invention, numerous specific details are given in the following specific embodiments. It will be understood by those skilled in the art that the present invention can also be implemented without these specific details.

[0031] In order to prove the creativity and technical value of the technical solution of the present invention, this section provides application examples of the claimed technical solution on specific products or related technologies.

[0032] The present invention provides an ultra-sensitive electronic skin based on a microporous structure and a preparation method thereof, comprising the following steps:

[0033] Step 1, adding titanium tetrachloride solution dropwise into ammonia water in a fume hood, adjusting the pH value of the solution to 8.0 to obtain white titanium dioxide gel, then dissolving the titanium dioxide gel in a mixed solution of oxalic acid, calcium carbonate, copper nitrate and acetone, filtering to obtain a blue colloid, and then calcining the blue colloid in a muffle furnace to obtain copper calcium titanate crystal powder;

[0034] Step 2, pouring sodium chloride and copper calcium titanate particles into a mortar for ball milling, pouring the mixed powder after ball milling into polydimethylsiloxane for uniform dispersion, and then coating the mixed viscous solution by screen printing to obtain a composite film material;

[0035] Step 3: Cut the composite film material of suitable size and place it in warm water to dissolve the sodium chloride microscopic particles in the film to obtain an organic / inorganic composite microporous film. Spray electrodes on the upper and lower surfaces of the film and connect wires to make an ultra-sensitive electronic skin.

[0036] Example 1

[0037] The present invention provides an ultra-sensitive electronic skin based on a microporous structure and a preparation method thereof, comprising the following steps:

[0038] Step 1, adding titanium tetrachloride solution dropwise into ammonia water in a fume hood, adjusting the pH value of the solution to 8.0 to obtain white titanium dioxide gel, then dissolving the titanium dioxide gel in a mixed solution of oxalic acid, calcium carbonate, copper nitrate and acetone, filtering to obtain a blue colloid, and then calcining the blue colloid in a muffle furnace to obtain copper calcium titanate crystal powder;

[0039] Step 2, pouring sodium chloride and copper calcium titanate particles into a mortar for ball milling, pouring the mixed powder after ball milling into polydimethylsiloxane for uniform dispersion, and then coating the mixed viscous solution by screen printing to obtain a composite film material;

[0040] Step 3: Cut the composite film material of suitable size and place it in warm water to dissolve the sodium chloride microscopic particles in the film to obtain an organic / inorganic composite microporous film. Spray electrodes on the upper and lower surfaces of the film and connect wires to make an ultra-sensitive electronic skin.

[0041] In the above scheme, in step 1, the calcination temperature in step 1 is 750° C., and the calcination atmosphere is air.

[0042] In the above scheme, the amounts of oxalic acid, calcium carbonate, copper nitrate, acetone and deionized water in step 1 are 0.08 mol, 0.01 mol, 0.03 mol, 40 ml and 100 ml respectively;

[0043] In the above scheme, in step 2, the calcium copper titanate needs to be ultrasonically treated and dried in a grinder.

[0044] In the above scheme, the screen printing mesh size in step 2 is 50 meshes.

[0045] In the above scheme, the size of the film cut in step 3 is 1*1*0.2mm 3 .

[0046] In the above scheme, the electrode material sprayed in step 3 is a mixture of silver nanoparticles and acrylic acid.

[0047] The ultra-sensitive electronic skin based on microporous structure and the electronic skin prepared by the preparation method provided by the embodiment of the present invention can be applied to the fields of intracranial pressure monitoring, electronic skin and motion recognition. The embodiment of the present invention has achieved some positive effects in the process of research and development or use, and it does have great advantages compared with the prior art. The following content is described in combination with the data, icons, etc. of the test process.

[0048] The electronic skin prepared in Example 1 is applied in the field of intelligent perception. Figure 2 The figure shows the comparison of the XRD spectrum of copper calcium titanate prepared in step 1 with the standard card. The peaks (200), (400), (422) and (440) can all correspond to the standard card, and the other small peaks can also correspond one by one, proving that the obtained nanopowder is copper calcium titanate. The dielectric constant of copper calcium titanate nanomaterials is as high as 10 4 This is mainly due to the boundary layer capacitance effect formed by the high-resistance grain boundaries and the semiconductor grains. Figure 3 and Figure 4It can be observed that after soaking in water and removing the sodium chloride particles, a porous and fluffy copper calcium titanate / polydimethylsiloxane film can be obtained. This porous structure makes the sensing material have good compressibility, which is also the guarantee for the high sensitivity of the electronic skin, and the introduction of high dielectric constant copper calcium titanate further improves the sensitivity of the sensing film. Through screen printing technology, we obtain a composite film with a thickness of less than 100μm, which gives the electronic skin prepared from it good flexibility and interface conformality. By coating metal electrodes on the surface of the composite film and leading out wires, it can be prepared into a capacitive electronic skin with high sensitivity. By applying different pressures on the surface of the electronic skin using a universal mechanical stretching machine, the sensing properties of the electronic skin can be studied, such as Figure 5 As shown in Figure 1, the electronic skin with a large number of microscopic holes can sensitively sense pressure changes from 0.1KPa to 20KPa. Figure 6 In the study, we found that due to the presence of microscopic holes, the electronic skin has good linearity, and its capacitance change rate increases with the increase of external pressure. The sensitivity in the range of 0.1KPa to 20KPa is as high as 30KPa- 1 In the study of its response time, it was found that this electronic skin can respond extremely sensitively to external stress, and its response time and recovery time are both about 200ms. The specific response performance is as follows Figure 7 Finally, in the cycle stability test, we found that this electronic skin with a large number of microscopic holes also has good cycle stability, such as Figure 8 As shown, after more than 600 cycles, the response of the electronic skin to the capacitor has basically not changed, indicating that the electronic skin designed with this microscopic hole structure not only has high sensitivity and linearity, but also has excellent stability, and can be widely used in the field of intelligent perception.

Claims

1. A method for preparing an ultra-sensitive, conformable electronic skin based on a microporous structure, characterized in that: The following steps are involved: Step 1, adding titanium tetrachloride solution dropwise into ammonia water in a fume hood, adjusting the pH value of the solution to 8.0 to obtain white titanium dioxide gel, then dissolving the titanium dioxide gel in a mixed solution of oxalic acid, calcium carbonate, copper nitrate and acetone, filtering to obtain a blue colloid, and then calcining the blue colloid in a muffle furnace to obtain copper calcium titanate crystal powder; Step 2, grinding sodium chloride and copper calcium titanate crystal powder together to obtain a mixed powder, then pouring the mixed powder into polydimethylsiloxane to evenly disperse it, and then coating the mixed viscous solution by screen printing to obtain a composite film material; Step 3: Cut the composite film material and place it in warm water to dissolve the sodium chloride microscopic particles in the film to form a microporous structure, thereby obtaining an organic / inorganic composite microporous film. Electrodes are sprayed on the upper and lower surfaces of the film and connected to wires to make an ultra-sensitive electronic skin.

2. The method for preparing an ultra-sensitive, conformable electronic skin based on a microporous structure according to claim 1, characterized in that: The calcination temperature in step 1 is 750° C., and the calcination atmosphere is air.

3. The method for preparing an ultra-sensitive, conformable electronic skin based on a microporous structure according to claim 1, characterized in that: In the step 1, the amounts of oxalic acid, calcium carbonate, copper nitrate, acetone and deionized water are 0.08 mol, 0.01 mol, 0.03 mol, 40 ml and 100 ml respectively.

4. The method for preparing an ultra-sensitive, conformable electronic skin based on a microporous structure according to claim 1, characterized in that: In the step 2, the calcium copper titanate needs to be ultrasonically treated and dried in a grinder.

5. The method for preparing an ultra-sensitive, conformable electronic skin based on a microporous structure according to claim 1, characterized in that: The screen printing mesh number in step 2 is 50 meshes.

6. The method for preparing an ultra-sensitive, conformable electronic skin based on a microporous structure according to claim 1, characterized in that: The size of the film cut in step 3 is 1*1*0.2mm 3 .

7. The method for preparing an ultra-sensitive, conformable electronic skin based on a microporous structure according to claim 1, characterized in that: The electrode material sprayed in step 3 is a mixture of silver nanoparticles and acrylic acid.

8. An ultra-sensitive, conformable electronic skin based on a microporous structure, characterized in that: The ultra-sensitive electronic skin is prepared by the method for preparing an ultra-sensitive electronic skin based on a microporous structure as described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • An inorganic / polydimethylsiloxane composite flexible material having a high dielectric constant, a preparing method thereof and applications of the material

    CN106497064A

  • Calcium copper titanate (CCTO) / polydimethylsiloxane (PDMS) composite flexible foam as well as preparation method and application thereof

    CN106928723A

  • Composite film material, friction nano-generator and preparation method and application of friction nano-generator

    CN116396513A

  • Flexible pressure sensor and preparation method thereof

    CN116625557A

  • Flexible pressure sensor simulating human skin, preparation method and system

    CN117848551A